Medical conditions underlying recurrence of retinal vein occlusion. - Dodson, P M (1985)
Seventeen patients with recurrent retinal vein occlusion were investigated for underlying medical conditions and compared with 61 patients with single retinal vein occlusion (26 with central, 35 with branch vein occlusion). The two study groups were comparable for age, sex, and weight. Patients with recurrence had a significantly increased prevalence rate of hypertension (88% versus 48%: p less than 0.01), with a trend to increased hyperlipidaemia (47% versus 33%) compared with patients with a single episode. A significantly raised mean systolic (p less than 0.05) but not diastolic blood pressure was found in patients with recurrence. Other cardiovascular risk factors in patients with recurrence were also found and included lower mean levels of high density lipoprotein (HDL)-cholesterol (p less than 0.02) and the HDL2 subfraction (p less than 0.001), and a significantly increased proportion of patients with regular alcohol intake (p less than 0.01). We conclude that hypertension and hyperlipidaemia with an increase in other cardiovascular risk factors are commonly found in patients with recurrent retinal vein occlusion and may therefore be important aetiological factors. The possible benefits of treatment of these underlying conditions to prevent recurrence need to be assessed in well designed prospective studies.